Computational study of C(sp3)–O bond formation at a PdIV centre. Issue 11 (6th March 2017) - Canty, Allan J.; Ariafard, Alireza; Camasso, Nicole M.; Higgs, Andrew T.; Yates, Brian F.; Sanford, Melanie S.
Abstract : This report describes a computational study of C(sp 3 )–OR bond formation from Pd IV complexes of general structure Pd IV (CH2 CMe2 - o -C6 H4 - C, C ′)(F)(OR)(bpy- N, N ′) (bpy = 2, 2′-bipyridine). Abstract : This report describes a computational study of C(sp 3 )–OR bond formation from Pd IV complexes of general structure Pd IV (CH2 CMe2 - o -C6 H4 - C, C ′)(F)(OR)(bpy- N, N ′) (bpy = 2, 2′-bipyridine). Dissociation of − OR from the different octahedral Pd IV starting materials results in a common square-pyramidal Pd IV cation. An SN 2-type attack by − OR ( − OR = phenoxide, acetate, difluoroacetate, and nitrate) then leads to C(sp 3 )–OR bond formation. In contrast, when − OR = triflate, concerted C(sp 3 )–C(sp 2 ) bond-forming reductive elimination takes place, and the calculations indicate this outcome is the result of thermodynamic rather than kinetic control. The energy requirements for the dissociation and SN 2 steps with different − OR follow opposing trends. The SN 2 transition states exhibit "Pd⋯C⋯O" angles in a tight range of 151.5 to 153.0°, resulting from steric interactions between the oxygen atom and the gem -dimethyl group of the ligand. Conformational effects for various OR ligands and isomerisation of the complexes were also examined as components of the solution dynamics in these systems. In all cases, the trends observed computationally agree with those observed experimentally.